Performance Management Antecedents and Public Sector Organizational Performance: Empirical Evidence from Nigeria - Abubakar, Abdulkadir; Saidin, Siti Zabedah; Ahmi, Aidi (International Journal of Economics and Financial Issues, 2016)
Using data from MDA-wide survey administered on the public sector organizations in the North-eastern part of Nigeria, the study examine some antecedents of the performance management practice and how these antecedents influenced public sector organizational performance. The hypotheses of the study were tested using the survey data from 63 public sector organizations notably ministries, departments and agencies (MDAs). Pearson zero-order correlation was used to analyze the hypothesized relationship. The study found that, certain antecedents such as performance measurement and institutional culture have significant positive association with public sector organizational performance. Thus, the study provides an avenue for MDAs in Nigeria and elsewhere to redesign, redefine and formulate policies for improving their hitherto unencouraging performance. The study also recommended that, more performance management mechanisms are needed to complement and improve the public sector efficiency. Keywords: Performance Management, Antecedents, Performance, Public Sector JEL Classifications: H11, H83